Analisis Fungsi Pengeluaran Pemerintah terhadap Tingkat Pertumbuhan Ekonomi Provinsi Jawa Timur - Heni Rahmawati (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2022)
Achieving of economic growth and development in a country is a goal to be achieved by a country. One of the economic data sets that are used as a reference in viewing the economic development of a region is to use economic data derived from Gross Domestic Regional Product. The value of GRDP reflects the potential for economic growth in a certain area. In achieving the goal of equitable growth and development, a budget or financing is needed to finance these development activities. These expenses are usually in the form of expenses for operational activities or investments. This research was conducted with the aim of observing and analyzing the impact of expenditures made by local government in relation to economic growth in east java province. This study uses a descriptive qualitative method and takes a sample of East Java government spending data for 2017-2020 and East Java GDRP Growth Rate data for 2017-2020. The results show that government spending affect the level of economic growth in an East Java Province.